Design of a Paper Money Counting Tool for the Infaq Charity Box of Syarikatul Anwar Mosque Based on the Internet of Things - Hafidzudin; Ari Nurul Alfian, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Mosque financial management, especially the calculation of charity box balances, is often done in a homemade manner so that it is less efficient and prone to errors. This research designed a prototype of a smart charity box based on the Internet of Effects (IoT) using a TCS3200 color detector to detect the nominal amount of bank notes automatically. The detection data is displayed in real-time via a web or Android application. The system integrates an Arduino microcontroller with a detector and a communication module to provide high accuracy in detecting money. As a result, the system is able to reduce primary workload, increase transparency, and speed up the calculation of mosque balances.